Responsible Pedagogy : Moving Beyond Authority and Mastery in Higher Education - Detweiler, Eric (Penn State University Press, 2022)
In recent decades, public higher education has faced perpetual crises. As states slash investment in postsecondary education and for-profit entities seek to supplant public colleges and universities, these public institutions have tried to compete by maximizing efficiency, namely, by downplaying and outsourcing the labor of teachers.Responsible Pedagogy makes a fresh case for the importance and value of public higher education and the work of teaching. In making this case, Eric Detweiler surveys the history of rhetoric and writing in postsecondary education, looking in particular at the teacher-student relationship. He finds that from the Socratic method to medieval exercises, from MOOCs to remote, asynchronous learning, the balance of authority and agency in the classroom is often precarious. But the problem goes deeper. Underlying both authority and agency is the value of mastery, which the teacher is to impart to the student. It is this emphasis on mastery, Detweiler argues, that distorts the proper relation between the student and teacher, a relationship in which they are responsible for and vulnerable to each other.Drawing on contemporary ethics, rhetorical theory, and critiques of practices in the online classroom, Detweiler develops a pedagogy of responsibility and shows how it can be applied in writing and communication curricula, assignments, and teacher-student interactions. Rehabilitating the proper role of the teacher, Responsible Pedagogy calls into question our newfound trust in educational technology and points the way to a better, more effective pedagogy.